EXAMINING THE ROLES OF GRAMMAR INSTRUCTION IN LANGUAGE TEACHING - Hervina, Hervina; Afdaleni, Afdaleni; Fadilla Taslim (Journal of Innovation Research and Knowledge, 2022)
Despite its possibility to help students understand how language is properly arranged, grammar instruction has been widely debated in the field of language teaching in terms of the necessity to engage students in such instruction. The opponent of this practice claim that it is ideal for students to acquire grammar through language exposure, and grammar instruction does not guarantee better production as it is evident in the previous grammar based language teaching method. However, others still maintain the importance of grammar instruction due to language complexity, which cannot be understood through exposure only, and its possibility to accelarate language comprehension. This present article makes an attempt to examine this view in this current language teaching practice. With the aim to see if grammar instruction is still needed and effective in the real practice, five English teachers were interviewed to obtain their view on grammar instruction in language teaching. From the interview, it is found that (1) teachers still believe grammar instruction is still important, (2) grammar is taught deductively with frequent error correction and use of L1, (3) grammar instruction is still effective to improve students’ language comprehension, and (4) grammar instruction needs to expose students to wide variety of structures with their language function. Therefore, it can be concluded that grammar instruction is still viewed important in today language practice but some improvement needs to be made